RANCANG BANGUN SISTEM MONITORING KECEPATAN PADA KAPAL TRIMARAN MENGGUNAKAN PIXHAWK - Mochammad Zaqi Arif; Edi Kurniawan; Shofa Dai Robbi (Majalah Ilmiah Teknologi Elektro, 2025)
Indonesia as a maritime nation with vast and strategic oceanic territory, continues to develop efficient and innovative ship technologies. This research focuses on the design and construction of a speed monitoring system for a trimaran vessel using the Pixhawk controller. The system integrates a Pixhawk autopilot unit as the main controller, an STM32 microcontroller for processing, dual BLDC motors, an internal combustion engine (ICE), and a remote control system. The Internet of Things (IoT) platform is employed for real-time data logging and monitoring. Experimental tests were conducted on five reference speed levels slow patrol, reconnaissance, medium patrol, cruising, and chase modes. Quantitative results show that the system achieved rapid response times at medium speeds, with stable operation and an average delay below 0.5 seconds. At high speeds, however, stability decreased by 15–20% due to environmental and load variations. Remote control communication maintained stable performance up to 210 meters with obstructions and 280 meters without obstacles. The results demonstrate that the system effectively supports real-time speed monitoring for trimaran vessels. The novelty of this study lies in the integration of hybrid propulsion and adaptive control within an IoT-based Pixhawk monitoring system, contributing to advancements in smart maritime technology.